Limitations of sorptivity and water permeability for the estimation of the chloride penetration rate in concrete regarding the accomplishment of prescriptive design for durability in the marine environment - Villagrán Zaccardi, Yury Andrés (2018)
This paper presents an analysis of experimental data from conventional concrete regarding sorptivity and penetrability under pressure comparing these paremeters to chloride diffusion rate determined in the laboratory and in actual marine environment. Prescriptions for durability assurance of reinforced concrete structures is based on the qualitative characterization of transport properties. For the specific case of the marine environment, it is required to assess the resistance of concrete to chloride ingress. The results show the limitations of both parameters as prescriptive indexes, with capillary absorption rate showing some advantages over water penetration under pressure.